2018
DOI: 10.3389/fgene.2018.00197
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Neuropeptides by Transcriptome and Proteome Analyses in a Bivalve Mollusc Patinopecten yessoensis

Abstract: Neuropeptides play essential roles in regulation of reproduction and growth in marine molluscs. But their function in marine bivalves – a group of animals of commercial importance – is largely unexplored due to the lack of systematic identification of these molecules. In this study, we sequenced and analyzed the transcriptome of nerve ganglia of Yesso scallop Patinopecten yessoensis, from which 63 neuropeptide genes were identified based on BLAST and de novo prediction approaches, and 31 were confirmed by prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 151 publications
(244 reference statements)
4
45
1
Order By: Relevance
“…The open reading frames (ORF) of allatostatin A1 and A2 cDNA sequences encoded deduced proteins of 114 and 129 amino acids with theoretical molecular mass of 12.60 and 14.06 kDa, respectively. The peptide precursor contains GxLamide at the C-terminal end, which is in agreement with a previous report on allatostatins A in D. reticulatum and P. yessoensis (Ahn et al 2017;Zhang et al 2018). Phylogenetic analysis revealed that buccalin precursors A1 and A2 of H. discus hannai were most closely related to D. reticulatum buccalin A1 and C. virginica buccalinlike neuropeptide precursors, respectively (Figure 1).…”
Section: Allatostatin a Or Buccalinsupporting
confidence: 90%
See 4 more Smart Citations
“…The open reading frames (ORF) of allatostatin A1 and A2 cDNA sequences encoded deduced proteins of 114 and 129 amino acids with theoretical molecular mass of 12.60 and 14.06 kDa, respectively. The peptide precursor contains GxLamide at the C-terminal end, which is in agreement with a previous report on allatostatins A in D. reticulatum and P. yessoensis (Ahn et al 2017;Zhang et al 2018). Phylogenetic analysis revealed that buccalin precursors A1 and A2 of H. discus hannai were most closely related to D. reticulatum buccalin A1 and C. virginica buccalinlike neuropeptide precursors, respectively (Figure 1).…”
Section: Allatostatin a Or Buccalinsupporting
confidence: 90%
“…In H. discus hannai, allatostatin B was identified. It was found to encode a 25-residue signal peptide followed by four putative allatostatin B peptides that contained conserved W residues at both ends, consistent with the results of previous studies (Ahn et al 2017;Zhang et al 2018).…”
Section: Allatostatin Bsupporting
confidence: 89%
See 3 more Smart Citations